3D Macroporous Oxidation‐Resistant Ti3C2Tx MXene Hybrid Hydrogels for Enhanced Supercapacitive Performances with Ultralong Cycle Life. (23rd November 2021) - Yang, Xue; Yao, Yiwei; Wang, Qian; Zhu, Kai; Ye, Ke; Wang, Guiling; Cao, Dianxue; Yan, Jun
Abstract: As a recently emerging group of 2D materials, MXene has attracted extensive attention in the energy storage field in recent years owing to their outstanding features. However, the notorious issues of inevitable oxidation stability and surface‐to‐surface self‐restacking for MXene significantly prevent its further wide‐ranging application. Herein, the 3D macroporous oxidation‐resistant Ti3 C2 T x MXene/graphene/carbon nanotube (MRC) hybrid hydrogels are prepared by a simple gelation method assisted by l ‐cysteine as crosslinker and l ‐ascorbic acid (VC) as reductant. Benefitting from the effectively alleviated restacking, excellent electrical conductivity, and the 3D inter‐crosslinked macroporous architecture, as a supercapacitor electrode, the obtained MRC aerogel exhibits a superior specific capacitance of 349 F g −1, unparalleled rate capability (52.0% at 3000 mV s −1 ) and amazing cyclic stability (retention of 97.1% after 100 000 cycles). Moreover, the 3D MRC‐30 aerogel exhibits an impressive oxidation‐resistant performance with just a 9.3% increase in electrical resistance after storing in ambient condition for 60 days, effectively alleviating the oxidation problem of MXene. This work demonstrates a new method for construction of 3D oxidation‐resistant MXene hydrogel, shedding new light on the promising applications of MXene materials, especially in high humidity and oxygen environment. Abstract : 3D macroporous oxidation‐resistant Ti3 C2 T x MXene/graphene/CNT hydrogels are prepared by a simple gelation method assisted by l ‐cysteine as a crosslinker and l ‐ascorbic acid as a reductant, which exhibit high specific capacitance of 349 F g −1 at 2 mV s −1, outstanding rate capability of 52.0% at 3000 mV s −1 as well as amazing cycling stability with capacitance retention of 97.1% after 100 000 cycles.